Microgravity and the intervertebral disc: The impact of space conditions on the biomechanics of the spine - Marfia, Giovanni; Guarnaccia, Laura; Navone, Stefania Elena; Ampollini, Antonella; Balsamo, Melissa; Benelli, Francesca; Gaudino, Chiara; Garzia, Emanuele; Fratocchi, Claudia; Di Murro, Claudia; Ligarotti, Gianfranco Kim; Campanella, Carmelo; et al. (Frontiers in Physiology, 2023)
The environmental conditions to which astronauts and other military pilots are subjected represent a unique example for understanding and studying the biomechanical events that regulate the functioning of the human body. In particular, microgravity has shown a significant impact on various biological systems, such as cardio-vascular system, immune system, endocrine system and, last but not least, the musculoskeletal. Among the potential risks of flying, low back pain (LBP) has a high incidence among astronauts and military pilots and it is often associated with intervertebral disc degeneration (IVD) events. The mechanisms of degeneration determine the loss of structural and functional integrity and are accompanied by the aberrant production of pro-inflammatory mediators that exacerbate the degenerative environment, contributing to the onset of pain. In the present work, the mechanisms of disc degeneration, the conditions of microgravity and their association will be discussed, in order to identify possible molecular mechanisms underlying disc degeneration and the related clinical manifestations, in order to develop a model of prevention to maintain air- and space-travelers health and performance. The focus on microgravity also allows the development of new proof of concepts with potential therapeutic implications.